The Poetical Works of John Keats - Keats, John (London ; New York : Macmillan and Co., 1889)
This text is a collection of the poetical works of John Keats, an English poet. It is reprinted from the original editions with notes by Francis T. Palgrave, who was a professor of poetry in the University of Oxford.
The Poetical Works of John Keats : reprinted from the original editions / with notes by Francis T. Palgrave. Professor of Poetry in the University of Oxford.
Comprising 284 pages, this copy has some staining and slight foxing, but it does not obscure the text.
Keywords: rare books, The Poetical Works of John Keats, John Keats, Poems